Documentation in conservation for the retouching process of a painting by Amadeo de Souza-Cardoso - Bailão, Ana (2017)
In the documentation in conservation context, there is an increasing demand for precise and accurate data and also for full three dimensional records of the cultural heritage. This paper presents the study case of a painting by Amadeo de Souza-Cardoso before, during and after the retouching treatment. The work focuses on the use of open source systems, such as GIS and photogrammetry software, in order to produce accurate maps of object losses and realistic virtual 3D models enabling the study of artworks with a minimum budget and a low cost infrastructure.